Sirtuin 3 (SIRT3) maintains bone homeostasis by regulating AMPK-PGC-1β axis in mice - Huh, Jeong-Eun (Sci Rep, 2016)
The mitochondrial sirtuin 3 (SIRT3) is involved in suppressing the onset of multiple pathologies, including cardiovascular disease, fatty liver, age-related hearing loss, and breast cancer. But a physiological role of SIRT3 in bone metabolism is not known. Here we show that SIRT3 is a key regulatory molecule to maintain bone homeostasis. Mice deficient in SIRT3 exhibited severe osteopenia owing to increased numbers of osteoclasts. Osteoclast precursors from Sirt3−/− mice underwent increased osteoclastogenesis in response to receptor activator of nuclear factor-κB ligand (RANKL), an essential cytokine for osteoclast differentiation. SIRT3 expression from RANKL induction depended on the transcription coactivator PGC-1β (peroxisome proliferator-activated receptor-γ co-activator-1β) and the nuclear receptor ERRα (estrogen receptor-related receptor α), and that SIRT3 inhibited the differentiation by interfering with the RANKL-induced expression of PGC-1β. Thus an auto-regulatory feedback mechanism operates to induce its own inhibitor SIRT3 by PGC-1β. Moreover, Sirt3−/− osteoclast precursors reduced AMP-activated protein kinase (AMPK) phosphorylation through down-regulating the expression of AMPK. Our results suggest that a mitochondrial SIRT3 is an intrinsic inhibitor for RANKL-mediated osteoclastogenesis.